Crystal structure of Ba2(La0.727Ba0.182M0.091)MO6 (M = Nb, Sb, Bi): symmetry nuance identified in photoluminescence and IR spectroscopy studies. Issue 5 (19th January 2017) - Phatak, Rohan; Gupta, Santosh K.; Maheshwari, Priya; Das, Amitabh; Sali, Sanjay K.
Abstract : A one-third lanthanum deficiency was created in Ba2 LaMO6 compounds to form Ba2 (La0.727 Ba0.182 M0.091 )MO6 compounds (M 5+ = Nb, Sb, and Bi) and the subsequent distortion of the octahedra was probed by various techniques. Abstract : A one-third lanthanum deficiency was created in Ba2 LaM 5+ O6 compounds (LaM compounds) to form Ba2 La2/3 M 5+ O5.5 compounds (La2/3M compounds) for M = Nb, Sb, and Bi. The compounds were prepared by a gel-combustion method using citric acid as a fuel. All the compounds were characterized by powder X-ray diffraction (XRD). The XRD analysis showed that the space group of the La2/3M compounds remains the same for the Bi and Sb samples when compared to the reported LaM compounds, except for the Nb sample. La2/3Nb and La2/3Sb adopt a rhombohedral structure with the space group R 3̄, whereas La2/3Bi adopts a monoclinic structure with the space group I 2/ m . As the positron annihilation spectroscopy (PALS) technique is sensitive to cation deficiency, it was used to detect the presence of cation vacancies in the samples, which are formed due to the decrease in the lanthanum concentration. The PALS analyses indicated that the absence of cation deficiency in the La2/3M compounds is similar to that observed in the LaM compound. Thus, the crystal structure of the La2/3M compound was modeled, such that the cation deficiency at the La site is filled by Ba 2+ and M 5+ ions, and the crystal structure formula is given as Ba2 (La0.727 Ba0.182 M0.091 )MO6 . This model was confirmed by Rietveld refinement of the XRD data. The emission spectra of Eu 3+ showed a strong dependence on its local site symmetry in the host material, in which it is being doped and this can be used as a spectroscopic probe for detecting any differences in the symmetry. Comparison of the local symmetry around La 3+ cation was studied using photoluminescence (PL) by doping 2 atom% Eu 3+ in LaM and La2/3M compounds. Infrared spectroscopy (IRS) analyses were also carried out for LaM and La2/3M compounds. There was complete agreement between the PL and IRS results and they were also in concordance with the predicted crystal structure model. Interestingly in these La2/3M compounds, the equilibrium structure prefers large Ba 2+ ion to occupy the octahedral B-site rather than forming an octahedral vacancy at that site, making these perovskite compounds rare and novel in their class.